Law Enforcement Efforts Against Fisheries Crime Under Specialist Lex Provisions in Indonesia - Siregar, Padian Adi (International Journal Reglement & Society (IJRS), 2020)
The 1945 Constitution (UUD) Article 33 paragraph (3) states,